Accuracy of the FY-L formula in calculating intraocular lens power after small-incision lenticule extraction - Hu, Yingfeng; Lin, Liqun; Zeng, Danqi; Wang, Yan; Zhang, Rong; Zhang, Zhe; Wang, Zheng; Zhang, Guangbin; Ye, Xiangyu (Frontiers in Medicine, 2023)
Purpose: To assess the FY-L formula's accuracy in calculating intraocular lens (IOL) power after small-incision lenticule extraction (SMILE). Methods: For the post-SMILE IOL calculation of the same eye, the IOL power targeting the pre-SMILE eyes' lowest myopic refractive error was used. The FY-L, the Emmetropia Verifying Optical Formula (EVO-L), the Barrett True-K no history, and the Shammas-L, respectively, were used to calculate the predicted refractive error of target IOL power. A comparison was made between the change in spherical equivalent induced by SMILE (SMILE-Dif) and the variance between IOL-Dif (IOL-Induced Refractive Error) before and after SMILE. The prediction error (PE) was defined as SMILE-Dif minus IOL-Dif. The proportion of eyes with PEs within ±0.25D, ±0.50D, ±0.75D, and ±1.00D, the numerical and absolute prediction errors (PEs and AEs), and the median absolute error (MedAE) were compared. Results: 80 eyes from 42 patients who underwent SMILE were included in the study.The FY-L formula generated the sample's lowest mean PE (0.06±0.76D), MAE (0.58±0.50D), and MedAE (0.47D), respectively. The PEs in ±0.25D, ±0.50D, ±0.75D, and ±1.00D comprised 28.8%, 46.3%, 70.0%, and 87.5% for the FY-L formula. Compared to other formulas, the FY-L formula produced the highest value with PEs for the percent of eyes in ±0.50D, ±0.75D, and ±1.00D. Conclusions: This study demonstrates that the FY-L formula provides satisfactory outcomes in estimating the IOL power in the eyes after SMLIE.